Smart composite detector of orbital debris and micrometeoroids particles. (2021) - De Simone, Mario Emanuele; Andreades, Christos; Meo, Michele; Ciampa, Francesco
Abstract: The presence of space debris and micrometeoroids particles in the space environment are a serious threat for Earth orbiting spacecraft. Hypervelocity impacts (HVIs) at the typical velocities of ∼7 to 10 km/s can severely damage or destroy satellites, so that debris detection systems are necessary. In the present research work, a "smart" composite detector of orbital debris and micrometeoroids particles is proposed and developed as proof-of-concept for future space missions. The presented detector consists of two thin parallel carbon fibre reinforced plastic (CFRP) composite plates, each instrumented with three piezoelectric transducers embedded into the laminate. The developed algorithm can estimate both directions and velocities of orbital debris and micrometeoroids particles by the knowledge of: (i) impact locations on the two plates, (ii) the time differences of arrival of acoustic emissions generated by impacts and (iii) the wave velocity profile in the composite plates. The localisation of the impact events is achieved by time reversal method, while the time of arrivals are calculated using Akaike Information Criterion method. A set of experimental tests were performed to validate the proof-of-concept using a small drop tower. Impact results showed the high accuracy of the proposed algorithm in the estimation of impact locations, directions and velocities of impact objects.